DNA‐Mediated Assembly of Multispecific Antibodies for T Cell Engaging and Tumor Killing. Issue 2 (23rd November 2019) - Pan, Liqiang; Cao, Chan; Run, Changqing; Zhou, Liujuan; Chou, James J.
Abstract: Targeting T‐cells against cancer cells is a direct means of treating cancer, and has already shown great responses in clinical treatment of B‐cell malignancies. A simple way to redirect T‐cells to cancer cells is by using multispecific antibody (MsAb) that contains different arms for specifically "grabbing" the T‐cells and cancer cells; as such, the T‐cells are activated upon target engagement and the killing begins. Here, a nucleic acid mediated protein–protein assembly (NAPPA) approach is implemented to construct a MsAb for T‐cell engaging and tumor killing. Anti ‐CD19 and ‐CD3 single‐chain variable fragments (scFvs) are conjugated to different l ‐DNAs with sequences that form the Holliday junction, thus allowing spontaneous assembly of homogeneous protein–DNA oligomers containing two anti‐CD19 and one anti‐CD3 scFvs. The new MsAb shows strong efficacy in inducing Raji tumor cell cytotoxicity in the presence of T‐cells with EC50 ≈ 0.2 × 10 −9 m ; it also suppresses tumor growth in a Raji xenograft mouse model. The data indicates that MsAbs assembled from protein–DNA conjugates are effective macromolecules for directing T‐cells for tumor killing. The modular nature of the NAPPA platform allows rapid generation of complex MsAbs from simple antibody fragments, while offering a general solution for preparing antibodies with high‐order specificity. Abstract : Herein, a general solution for generating multispecific antibodies with N degree of specificity is reported. The method is used to generate a multispecific antibody containing two anti‐CD19 and one anti‐CD3 antibody fragments (scFvs). The new multispecific antibody shows strong efficacy in mediating Raji tumor cell cytotoxicity in the presence of human T‐cells both in vitro and in vivo.